[REVIEW]: Krzysztof Bracha, Maria Mediatrix – Maria Adiutrix. Pobożność maryjna w nauczaniu kaznodziejskim w Polsce późnego średniowiecza. Sermones dominic ales et festivales z tzw. kolekcji Piotra z Miłosławia, Wydawnictwo DiG, Warszawa 2023, pp. 328. - Kaczor, Ewelina (Acta Mediaevalia. Series Nova, 2024)
Review of Krzysztof Bracha's monograph: Maria Mediatrix – Maria Adiutrix. Marian Devotions in the Teachings of Late Medieval Preaching in Poland. The Sermones dominicales et festivals from the So-called Collectione of Piotr of Miłosław, Warszawa 2023